PROSES PEMBELAJARAN REOG KENDANG TULUNGAGUNG PADA MATA KULIAH REOG KENDANG: STUDI DESKRIPTIF KUALITATIF MELALUI METODE PENGAMATAN - Talitha Adine Ardiningrum; Ammy Aulia Renata Anny (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Reog Kendang is a traditional performing art originating from Tulungagung, Indonesia, distinguished by the unique integration of expressive dance movements and synchronized percussion rhythms performed by the dancers themselves. As part of an academically grounded preservation effort, this traditional art has been incorporated into the higher education curriculum through the Reog Kendang course. This study aims to provide an in-depth description of the learning process of Reog Kendang in this course, with a particular focus on movement transmission, rhythm mastery, and the challenges encountered by university students. A descriptive qualitative research design was employed. Data were collected through passive participant observation conducted over one academic semester and in-depth interviews with students from the Elementary School Teacher Education (PGSD) Study Program at Universitas Bhinneka PGRI Tulungagung who were enrolled in the Reog Kendang course. The findings revealed that the transmission of dance movements was carried out primarily through a demonstration–imitation (modeling) approach combined with verbal rhythmic counting. Students experienced a dual-focus (split-attention) challenge, as they were required to maintain consistent dhong–dhang drum patterns while simultaneously performing dynamic footwork and coordinated body movements. The learning process not only facilitated the acquisition of motor skills but also fostered the internalization of collective values, teamwork, discipline, and physical endurance among the students. These findings suggest that the Reog Kendang course serves not only as a medium for preserving local cultural heritage but also as an effective pedagogical approach for developing students' artistic competence, collaborative skills, and cultural awareness in higher education.